INTERGASI PROGRAM ONE DAY ONE STORY DENGAN JURNAL REFLEKSI UNTUK PENGUATAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Syafruddin Muhtar; Dewi, Yunita Ratna; Tasya Febri Anasti; Siti Fansuri; Rista; Zulfa Jahiya Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of integrating the One Day One Story program with reflective journaling in improving elementary school students’ reading literacy. The research employed a qualitative descriptive approach. The subjects of the study were fifth-grade students at SDN 2 Kuranji Mataram, consisting of 23 students. Data were collected through observation, interviews, and documentation. The results indicate that the One Day One Story program is effective in enhancing students’ reading interest. The program was implemented for 15 minutes before the learning process began, using short stories that were engaging and appropriate to the students’ characteristics. The use of reflective journals helped students understand the content of the texts and develop their critical thinking skills. Prior to the implementation of the program, only 5 out of 23 students showed an interest in reading, indicating a low level of reading literacy. After the program was implemented, there was a noticeable increase in students’ engagement and enthusiasm in reading activities. Therefore, this program is recommended to be implemented continuously as a strategy to strengthen reading literacy in elementary schools.